Elevated neutrophil-to-lymphocyte ratio predicts poorer histopathological differentiation in colorectal cancer: a study from a Southeast Asian Tertiary Hospital - Edwin Saleh Siregar; Muhammad Al Anas; Dedy Hermansyah (Medicinski glasnik, 2026)
Aim: of this study was to evaluate the correlation between pre-treatment NLR and histopathological differentiation in colorectal cancer, and to assess the diagnostic accuracy of NLR as a predictive biomarker. Methods: A retrospective study was conducted at Adam Malik Haji Center General Hospital Medan, North Sumatera. Medical records of 45 colorectal cancer patients treated between January and December 2024 were reviewed. Pre-treatment NLR values were calculated from peripheral blood counts. Receiver Operating Characteristic (ROC) curve analysis was performed to determine diagnostic performance, and correlation analysis was used to assess the relationship between NLR and tumour grade. Results: The mean NLR was 6.33±4.92. ROC analysis yielded an area under the curve (AUC) of 0.874, indicating excellent diagnostic ability. An NLR cutoff value of 6.25 provided a sensitivity of 87.5% and specificity of 72.5% for predicting poor histopathological differentiation. A moderate positive correlation (r=0.612; p<0.001) was found between higher NLR values and poorer differentiation. Conclusion: Pre-treatment NLR correlated with histopathological grade and showed promise as a simple, non-invasive biomarker for assessing tumour aggressiveness in colorectal cancer.
Keywords: biomarkers; Tumor; inflammation; prognosis; survival analysis